Coseismic Displacement Accumulation Between 1996 and 2019 Using A Global Empirical Law on Indonesia Continuously Operating Reference Station (InaCORS) - Cecep Pratama; Febrian Fitryanik Susanta; Ridho Ilahi; Alian Fathira Khomaini; Hadi Wijaya Kusuma Abdillah (Jurnal Geospasial Indonesia, 2019)
Indonesia archipelago is one of the most populated country with active and complex tectonic zone in the world. Plate boundaries were assembled by four major plate which made the region not only vulnerable to earth-hazard but also prone to semi-dynamic reference frame. However, influence of transient deformation such as coseismic displacement due to large amount of small to intermediate earthquakes (< Mw 6) on the geodetic networks is remain poorly understood. Geospatial Information Agency occupied permanent and continuous GPS networks since 1996 but rapidly increase in 2010. Based on simulated empirical law of coseismic crustal deformation, we estimate the cumulative displacement due to coseismic step on Indonesia Continuous Operating Reference Stations (InaCORS). We utilize the position of the observation network and earthquake hypocentral with estimated moment magnitude. Our result suggesting small to intermediate earthquakes are indispensable for estimating secular motion and potentially contribute the cumulative offset associated with the transient postseismic deformation.